FEMINISM NATIONAL IDENTITY - Hoda Rouhana (Jurnal Ilmiah Peuradeun, 2015)
In this article, I address paradoxes and ambiguities that result from this double oppression, and discuss some of the questions that arise from the formulation of this dichotomy, which forces women to choose between feminist and nationalist agendas. I discuss who formulates this dichotomy, who identifies nationalism and feminism, and who benefits from this identification. To address these topics, I discuss two specific examples: Muslim women in India and Palestinian women within Israel. The reformulation of nationalist/religious identity in such a way as to make it compatible with a feminist perspective is a very important project. Such a project must be built on changing the dominant culture from within. Such a process is long-term, however, and until it is achieved, women will continue to suffer. We cannot demand that oppressed women wait until the rebuilding of the dominant culture is completed. In reality, there is the possibility that utilizing secular courts will force national/ religious institutions to make positive changes.